Burn [large type] - Barr, Nevada (Barr, Nevada. Anna Pigeon novel., 2010)
Recovering from recent emotional trauma, National Park Service ranger Anna Pigeon goes to New Orleans to visit her friend, Geneva, only to become the target of a dark curse, prompting her to investigate what it has to do with a fugitive mother accused of killing her family.